Development of Microbial Ecological Theory: Stability, Plasticity, and Evolution of Microbial Ecosystems - Shin Haruta (Frontiers Research Topics, 2017)
"How can we develop microbial ecological theory?" The development of microbial ecological theory has a long way to reach its goal. Advances in microbial ecological techniques provide novel insights into microbial ecosystems. Articles in this book are challenging to determine the central and general tenets of the ecological theory that describes the features of microbial ecosystems. Their achievements expand the frontiers of current microbial ecology and propose the next step. Assemblage of these diverse articles hopefully helps to go on this long journey with many avenues for advancement of microbial ecology.